Antidiabetic and Hypolipidemic Effects of Millettia leucantha Kurz Extract on Streptozotocin-induced Diabetic Rats - สกุลใจตรง สุภาษร (Progress in Applied Science and Technology, 2017)
The effects of Millettia leucantha Kurz extract (MLE) on hypoglycemic and hypolipidemic effects in diabetic rats were carried out in male Wistar rats induced by a single intraperitoneal injection of 65 mg/kg b.w. of streptozotocin. The rats were randomly assigned into five groups (n = 8); namely: normal rats treated with distilled water, normal rats treated with MLE (300 mg/kg b.w.), diabetic rats treated with distilled water, diabetic rats treated with Glibenclamide (0.5 mg/kg b.w.) and diabetic rats treated with MLE (300 mg/kg b.w.). MLE was administered orally and daily to the rats for eight weeks. The blood glucose and body weight of the rats were measured weekly. After eight weeks of treatment, the lipid profiles were determined using an automatic blood chemical analyzer. The serum insulin were determined using the Radioimmunoassay kit. Statistical analysis of the data showed that MLE significantly (p<0.05) decreased blood glucose in the diabetic rats with a similar potent to Glibenclamide. And also, MLE significantly (p<0.05) decreased Total cholesterol (TC), Triglyceride (TG) and Low-density lipoprotein cholesterol (LDL-C). However, it increased the body weight, High-density lipoprotein cholesterol (HDL-C) and serum insulin in the diabetic rats. These results suggest that MLE has antidiabetic and hypolipidemic effects in the diabetic rats.